EXPLORING THE EXPEDIENCY OF BLOCKCHAIN-BASED SOLUTIONS: REVIEW AND CHALLENGES - Francisco Javier MORENO ARBOLEDA; Georgia GARANI; Sergio Andrés ARBOLEDA ZULUAGA (Applied Computer Science)
A distributed type of database where digital data is stored as blocks chained together is called a Blockchain. Each block consists of several transactions, authenticated using cryptographic keys, and approved by a group of validators. Hundreds of different Blockchain solutions have been proposed over the years, proving that they attract research and business interest. In this article, the authors present a generic vocabulary for unifying different terminologies used by various researchers in the field, followed by a review and evaluation of several research works presenting Blockchain-based solutions. A set of criteria regarding usefulness and suitability of adopting a Blockchain application are distinguished in these works. A method to examine their applicability is also discussed. Cryptocurrencies and supply chains, the two most well-known Blockchain uses, are considered and examined to assess how important these criteria are in these two use cases.